Physiotherapy Effectiveness on Muscle Strength, Flexibility, Pain and Function in Patients with Patellofemoral Pain Syndrome - Konstantinos Papadopoulos; Russell Kabir (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2016)
Study objectives: To evaluate the effectiveness on muscle strength, flexibility, pain and function of a six-week physiotherapy treatment for patients with Patellofemoral Pain Syndrome delivered in a district North-West Wales National Health Service Hospital.  Methods: 26 patients with Patellofemoral Pain Syndrome (9 males, 16 females) who were referred to the NHS physiotherapy department where asked to complete an AKP Scale and two VASs along with a series of clinical tests that measure lower limb isometric strength and flexibility in two different occasions; The first occasion took place directly after the first treatment session with the physiotherapist; the second occasion took place directly after the last physiotherapy visit which was approximately after 5-8 weeks. Results: The data showed that physiotherapy treatment in patients with PFPS did not improve strength (measured by the lower limb isometric strength tests or flexibility (measured by the modified Thomas and hamstrings flexibility test) however; pain measured by two VASs (one for usual pain and one for pain on the day of the assessment) and function measured by the AKP Scale function, were significantly improved (VASs p<0.02 & AKP Scale p<0.01 ). Conclusions: This study reported that physiotherapy treatment in patients with PFPS works, not through strength and flexibility but through other components. There are several possible explanations for the results of this study. Future studies should aim to identify the different treatment components and which of these really work for patients with PFPS.